2000
DOI: 10.1007/s007260050024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the site of glucocorticoid action on neutral amino acid transport in superficial nephrons of rat kidney

Abstract: Glucocorticoid hormones enhance the reabsorptive capacity of filtered amino acids in rat kidney, as it was shown in previous in vivo clearance experiments. In the present study, the site of glucocorticoid action on neutral amino acid transport in superficial nephrons of rat kidney was investigated using in vivo micropuncture technique. Adult female Wistar rats were treated with dexamethasone (DEX), and fractional excretion of L-glutamine (L-Gln) and L-leucine (L-Leu) were determined and related to inulin after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Glucocorticoids have other important actions on renal function (e.g. downregulation of sodium/phosphate cotransport, 33 sulphate cotransport 34 and sodium effects on amino acid transport 35 ), as well as effects on acid–base, 36 including upregulation of the sodium/bicarbonate cotransporter, 37 but these effects are beyond the scope of the present review.…”
Section: Effects Of Cortisol On Renal Function and Renal Haemodynamicsmentioning
confidence: 94%
“…Glucocorticoids have other important actions on renal function (e.g. downregulation of sodium/phosphate cotransport, 33 sulphate cotransport 34 and sodium effects on amino acid transport 35 ), as well as effects on acid–base, 36 including upregulation of the sodium/bicarbonate cotransporter, 37 but these effects are beyond the scope of the present review.…”
Section: Effects Of Cortisol On Renal Function and Renal Haemodynamicsmentioning
confidence: 94%
“…Broer et al [29] found increased 4F2hc mRNA levels and enhanced L-type amino acid transport activity in phorbol esters-treated lymphocytes. The glucocorticoid dexamethasone was found to induce both the activity and expression of 4F2hc in the rat kidney [2]. Arginine depletion increased TA1/LAT1 mRNA expression, accompanied with no appreciable response of 4F2hc in rat hepatic cell lines [30].…”
Section: Discussionmentioning
confidence: 93%
“…Steroid hormones have been shown to enhance or diminish amino acid transport depending on the nature of the hormone. Micropuncture studies revealed a glucocorticoidinducible transport system for neutral amino acids mainly located in proximal straight tubules of rat kidney [2]. Dexamethasone was found to induce both the activity and expression of transport system y + LAT1 [2,3].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation